Effect of axial prestretch and adipose tissue on the inflation-extension behavior of the human abdominal aorta - Voňavková, Tereza; Horný, Lukáš (Computer methods in biomechanics and biomedical engineering, 2020)
Our study aims to show that perivascular adipose tissue may significantly change the mechanical state of the abdominal aorta. To this end, uniaxial tensile tests with perivascular fat tissue were carried out. In the subsequent regression analysis, stress-strain data were fitted by the polynomial strain energy density. A constitutive model of adipose tissue was used in the analytical simulation of the inflation-extension behavior of the human abdominal aorta. The computational model was based on the theory of the bi-layered thick-walled tube. In addition to the effect of perivascular tissue, the effect of axial prestretch was also studied. It was found that the presence of perivascular tissue reduces the distensibility of the aorta. Axial prestretch applied to the aorta embedded in adipose tissue had an effect opposite to that of adipose tissue. Axially prestrained aorta exhibited higher distensiblity than non-prestrained aorta. It was also shown that the perivascular envelope bears some portion of the pressure loading and thus reduces the mechanical stresses inside the wall of aorta. A similar effect was found for axial prestretch.
Keywords: Stress, Mechanical; dospělí; biomechanika; aorta abdominalis; Humans; lidé středního věku; Middle Aged; Aorta, Abdominal; Algorithms; tuková tkáň; mechanický stres; Adipose Tissue; mužské pohlaví; Adult; ženské pohlaví; lidé; Aged; senioři; Male; Biomechanical Phenomena; algoritmy; Female